1986
DOI: 10.1126/science.233.4759.85
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Fields at Uranus

Abstract: The magnetic field experiment on the Voyager 2 spacecraft revealed a strong planetary magnetic field of Uranus and an associated magnetosphere and fully developed bipolar masnetic tail. The detached bow shock wave in the solar wind supersonic flow was observed upstream at 23.7 Uranus radii (1 R(U) = 25,600 km) and the magnetopause boundary at 18.0 R(U), near the planet-sun line. A miaximum magnetic field of 413 nanotesla was observed at 4.19 R(U ), just before closest approach. Initial analyses reveal that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
242
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 372 publications
(244 citation statements)
references
References 38 publications
2
242
0
Order By: Relevance
“…Podolak et al (1990) suggested a stably stratified interior model instead. Nevertheless, a convective layer of a conducting material is needed to sustain a magnetic dynamo and to produce the quadrupolar fields observed for Uranus and Neptune (Ness et al 1986(Ness et al , 1989Connerney et al 1987Connerney et al , 1991. Water is assumed to be the dominant species in the layer where magnetic fields of ice giant planets are generated.…”
Section: Introductionmentioning
confidence: 99%
“…Podolak et al (1990) suggested a stably stratified interior model instead. Nevertheless, a convective layer of a conducting material is needed to sustain a magnetic dynamo and to produce the quadrupolar fields observed for Uranus and Neptune (Ness et al 1986(Ness et al , 1989Connerney et al 1987Connerney et al , 1991. Water is assumed to be the dominant species in the layer where magnetic fields of ice giant planets are generated.…”
Section: Introductionmentioning
confidence: 99%
“…As an illustrative example, we pick case 2 in (42b), when u>kz = 1-56172. Choosing the traveling wave speed V = 1, the traveling wave solutions of (51) show quasiperiodic behavior as shown in Fig. 14.…”
Section: Basic Equationsmentioning
confidence: 99%
“…The complex magnetic field of these planets can be approximated to fairly good accuracy by a dipole field that is off-center and tilted (relative to the rotation axis) [Ness et al, 1986[Ness et al, , 1989. A first and preliminary magnetic field model for Neptune is Ness et al 's [1989] offset, tilted dipole (OTD) model, which is well suited for describing the overall largescale magnetic field and is useful for studying the magnetospheric plasma as a first approximation.…”
Section: Introductionmentioning
confidence: 99%